Cultural Renewal in Early Modern Ottoman Jewish Life: Music, Devotional Singing, and the Pizmonim Genre - Samet, Hadar Feldman (European journal of jewish studies, 2025)
The current study explores the history of early modern Ottoman Jews through the lens of musically performed traditions as demonstrated in one of their most prominent and widely circulated sources—song-text collections. The scrutinized repertoire illuminates the practice of devotional singing as manifestation of social transformations and subtle innovative developments, both within Jewish life and its surroundings, reflected by and brought about through musical traditions. The cross-cultural and multifaceted historical examination of Ottoman Jews’ singing repertoire presents the gradual shift to an intensified emphasis on performance and sensorial-affective dimensions, rather than on poetic structures and particularistic content, during the seventeenth century. By exploring the production of the pizmonim genre, perspectives on it as acts of renewal, and its relation to Ottoman emotional ecology, this study offers new frameworks for understanding early modern Ottoman Jewish culture and society, and the mechanism of so-called decline versus novelty in this context.